Role of Piezoelectricity in Disease Diagnosis and Treatment: A Review - Tripathi P.; Dubey A.K. (My University, 2025)
Because of their unique electromechanical coupling response, piezoelectric smart biomaterials demonstrated distinctive capability toward effective, efficient, and quick diagnosis and treatment of a wide range of diseases. Such materials have potentiality to be utilized as wireless therapeutic methods with ultrasonic stimulation, which can be used as self-powered biomedical devices. An emerging advancement in the realm of personalized healthcare involves the utilization of piezoelectric biosensors for a range of therapeutic diagnosis such as diverse physiological signals in the human body, viruses, pathogens, and diseases like neurodegenerative ones, cancer, etc. The combination of piezoelectric nanoparticles with ultrasound has been established as a promising approach in sonodynamic therapy and piezocatalytic therapeutics and provides appealing alternatives for noninvasive treatments for cancer, chronic wounds, neurological diseases, etc. Innovations in implantable medical devices (IMDs), such as implantable piezoelectric energy generator (iPEG), offer significant advantages in improving physiological functioning and ability to power a cardiac pacemaker and restore the heart function. This comprehensive review critically evaluates the role of piezoelectricity in disease diagnosis and treatment, highlighting the implication of piezoelectric smart biomaterials for biomedical devices. It also discusses the potential of piezoelectric materials in healthcare monitoring, tissue engineering, and other medical applications while emphasizing future trends and challenges in the field. © 2024 American Chemical Society.